1995
DOI: 10.2508/chikusan.66.705
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Porcine Embryos after Thawing at Various Temperatures with Freezing Slowly

Abstract: Fig. 2. Correlationof cell numbers and diameters of porcine expanded blastocysts cultured in vitro either for less than 15h or more than 15h.(A) Correlation coefficient of cell numbers and diameters of the expanded blastocysts cultured for less than 15h was 0.966 (P<0.0001).(B) Correlation coefficient of cell numbers and diameters of the expanded blastocysts cultured for more than 15h was 0.705 (P=0.0766).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A reliable method of evaluating embryo quality is to assess the number of cells, but in porcine embryos this procedure requires fixation and staining, which produce unviable embryos. We did not evaluate the relationship between diam et er measurement (or morphological assessment) and embryo quality (number of cells) because Iwasaki et al [11] already reported that these two parameters are positively correlated. Establishment of embryo quality assessment by measurement of cell numbers without fixation (by live staining) may be advantageous in the field of embryo collection and transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reliable method of evaluating embryo quality is to assess the number of cells, but in porcine embryos this procedure requires fixation and staining, which produce unviable embryos. We did not evaluate the relationship between diam et er measurement (or morphological assessment) and embryo quality (number of cells) because Iwasaki et al [11] already reported that these two parameters are positively correlated. Establishment of embryo quality assessment by measurement of cell numbers without fixation (by live staining) may be advantageous in the field of embryo collection and transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of embryo diameter is a reliable way of estimating developmental stage [10][11][12], but the precise relationship between length of time after treatment with hormone(s) and embryo diameter has not yet been investigated.…”
mentioning
confidence: 99%
“…This assessment was used in our previous report [7]. Although it is important to confirm development during in vitro culture, the development may be influenced by culture conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…If younger-stage embryos were recovered, the embryos were obliged to incubate in vitro until the embryos developed to expanded blastocysts. However, the in vitro incubation, of which period is varied depending on the initial stage, adversely affects the freezing tolerance as well as the in vivo survival, while the longer the embryos incubate the larger the diameter of the embryos expands and the less the velocity of growth (an increase of number of viable nuclei) advances [7]. They demonstrated that the diameter had a good correlation with the number of viable nuclei, and that the adverse effect of incubation on freezing tolerance was almost negligible if incubation period for Day 6 embryos was limited to less than 15 h [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation